Prolonged Right Ventricular Outflow Tract Endocardial Activation Duration and Presence of Deceleration Zones in Patients With Idiopathic Premature Ventricular Contractions. Association With Low Voltage Areas - Parreira, Leonor; Carmo, Pedro; Marinheiro, Rita; Mesquita, Dinis; Farinha, José; Esteves, Ana; Amador, Pedro; Ferreira, António; Fonseca, Marta; Caria, Rui; Adragao, Pedro (Frontiers in Physiology, 2021)
Background and aims: The wavefront propagation velocity in the myocardium with fibrosis is characterised by the presence of deceleration zones and late activated zones, that are absent in the normal myocardium. Our aim was to study the right ventricular outflow tract (RVOT) endocardial activation duration in sinus rhythm, and assess the presence of deceleration zones, in patients with premature ventricular contractions (PVCs) and in controls. Methods: We studied 29 patients with idiopathic PVCs from the outflow tract, subjected to catheter ablation that had an activation and voltage map of the RVOT in sinus rhythm. A control group of 15 patients without PVCs that underwent ablation of supraventricular arrhythmias was also studied. RVOT endocardial activation duration and number of 10 ms isochrones across the RVOT were assessed. Propagation speed was calculated at the zone with the higher number of isochrones per cm radius. Deceleration zones were defined as zones with>3 isochrones within 1 cm radius. Low voltage areas were defined as areas with local electrogram with amplitude <1.5 mV. Results: The two groups did not differ in relation to age, gender or number of points in the map. RVOT endocardial activation duration and number of 10 ms isochrones were higher in the PVC group; 56 (41-66) ms vs 39 (35-41) ms, p=0.001 and 5 (4-8) vs 4 (4-5), p=0.001. Presence of deceleration zones and low voltage areas were more frequent in the PVC group; 20 (69%) vs 0 (0%), p<0.0001 and 21 (72%) vs 0 (0%), p<0.0001. The wavefront propagation speed was significantly lower in patients with PVCs than in the control group, 0.35 (0.27-0.40) vs 0.63 (0.56-0.66) m/s, p<0.0001. Patients with low voltage areas had longer activation duration 60 (52-67) vs 36 (32-40) ms, p<0.0001, more deceleration zones, 20 (95%) vs 0 (0%), p<0.0001, and lower wavefront propagation speed, 0.30 (0.26-0.36) vs 0.54 (0.36-0.66) m/s, p=0.002, than patients without low voltage areas. Conclusions: Right ventricular outflow tract endocardial activation duration was longer, propagation speed was lower and deceleration zones were more frequent in patients with PVCs than in controls and were associated with the presence of low voltage areas.